The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.cagd.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Bézier motions with end-constraints on speed

Abstract: • Finding a motion for given precision poses and speeds is discussed • Additive combinations of control poses are used within a geometric algebra • Analogies with the case of curve-fitting are shown

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In order to be able to join motion segments together smoothly, it is necessary to know the derivative of a motion at the ends of its segment. This is straightforward and well-known for an additive Bézier segment as in (18).…”
Section: Motion Constructionmentioning
confidence: 88%
See 1 more Smart Citation
“…In order to be able to join motion segments together smoothly, it is necessary to know the derivative of a motion at the ends of its segment. This is straightforward and well-known for an additive Bézier segment as in (18).…”
Section: Motion Constructionmentioning
confidence: 88%
“…Recent research has shown that free-form motions can be constructed through additive combinations of even-grade elements [17] and end-conditions for such additive motions have been investigated geometrically [18]. Many of the existing techniques from curve design, such as interpolation, naturally move over into motion design.…”
Section: Introductionmentioning
confidence: 99%